Leiomyoma Ablation with Transvaginal Ultrasonography-Guided Radiofrequency: A Report of Four Cases : Ablasi Mioma dengan Radiofrekuensi Terpandu Ultrasonografi Transvaginal: Laporan Empat Kasus - Doddy Sutanto; Ery Surya Sevriana; Rukmono Siswishanto; Lydia Olivia; Rahmalina (Indonesian Socety of Obstetrics and Gynecology, 2023)
Abstract Objective : To perform transvaginal ultrasound-guided radiofrequency ablation (RFA) to four women with symptomatic subserous and intramural leiomyomas using standard protocols. Methods : A report of four cases. Case : This article reports three of four women with leiomyomas had heavy menstruation bleeding. The first case was a premenopausal woman with pelvic discomfort. In the second case, the patient underwent curettage after being diagnosed with a blighted ovum, the third case with non-cyclic pain and irregular cycles, and the fourth case with 14-year-old infertility and repeated IVF failure. No significant side effects or complications occurred after treatment and during observation. Monitoring uterine leiomyoma size for one week and three months showed an average reduction of 56.9%, indicating a significant reduction in myoma volume. The reported symptoms also improved. Conclusion : Transvaginal ultrasound-guided radiofrequency ablation is an effective, non-invasive therapy with minimal side effects, so it may be the primary choice for leiomyoma therapy. Keywords : Leiomyoma, RFA, transvaginal ultrasonography Abstrak Objektif : Untuk melakukan radiofrekuensi ablasi (RFA) terpandu ultrasonografi transvaginal pada empat wanita dengan mioma intramural dan suberosa bergejala dengan menggunakan protokol yang standar. Metode : Laporan empat kasus. Kasus : Melaporkan tigas dari empat wanita dengan mioma uteri mengalami perdarahan menstruasi yang banyak. Kasus pertama adalah seorang wanita premenopause dengan keluhan rasa tidak nyaman pada panggul. Pada kasus kedua, pasien menjalani kuretase setelah didiagnosis dengan blighted ovum, kasus ketiga dengan nyeri non-siklus dan siklus tidak teratur, dan kasus keempat adalah infertilitas 14 tahun dan kegagalan IVF berulang. Tidak ada efek samping yang berarti atau komplikasi yang terjadi setelah tindakan dan selama pemantauan. Pemantauan ukuran mioma uteri selama satu minggu dan tiga bulan menunjukkan penurunan rata-rata sebesar 56,9%, menunjukkan penurunan volume mioma yang signifikan. Gejala-gejala yang dilaporkan juga mengalami perbaikan. Kesimpulan : Radiofrekuensi ablasi terpandu ultrasonografi transvaginal merupakan terapi non-invasif yang efektif dengan efek samping minimal, sehingga dapat menjadi pilihan utama untuk terapi mioma uteri. Kata kunci : Mioma, RFA, ultrasonografi transvaginal